Levantamento de doenças da alface americana em municípios do sul do estado de Minas Gerais - Pacifico, Marina Guimarães (2017)
Lettuce (Lactuca sativa L.) is the most abundant leafy vegetable, in planted area and volume produced. Domestic production is more than 1.5 million tons / year. One of the greatest difficulties in lettuce cultivation is the occurrence of diseases, which damage leaves and the root system, preventing absorption of water and nutrients and consequently, reduces the quality and productivity of the crop. In order to mitigate the damage caused by plant pathogens, it is necessary to establish efficient disease management programs, whose foundation is in the correct diagnosis of the main diseases and to know their temporal progress. Thus, this study aimed to survey the occurrence of diseases over time and establish their relationship with environmental variables. The experiment was conducted in seven properties located between the regions of Três Pontas (MG) and Boa Esperança (MG), in iceberg lettuce producers. Collections were done every 30 days, covering all lots of each property, for a year, covering the six cycles of the crop and diseases occurring in summer and winter. In total, 13 diseases affecting lettuce culture were found. Diseases of bacterial etiology represented 39%, fungi 34%, viruses 19% and nematodes 8%. Among the nematodes found, Meloidogyne javanica and M. incognita were present in 42.85% of the properties, while M. arenaria in 28.57%. The total number of occurrence reports was 1226, with Bacterial leaf spot being the most frequent (24.7%) and 303 reports. Spotted wilt was the second most frequently reported disease (233), occurring at 19%, but always observed throughout the year and in the younger lots of 7 to 14 DAT (days after transplanting). The species of Tospovirus found in the seven properties were TCSV and GRSV. In addition, no Tospovirus were found in plants in the nursery. Xanthomonas axonopodis pv. vitians occurred at high frequencies throughout the year, however the lower frequencies were observed at low temperatures. The highest frequencies of occurrence of Fusarium oxysporum f. sp. lactucae were in cold seasons.